Awandá e o feitiço da chicha: uma etnografia dos Makurap no Rio Guaporé - Castro, Breno Duarte (2023)
This text is an ethnographic work carried out with the Makurap people, who speak the Tupi-Tupari language, and who inhabit the right bank of the Guaporé River in the Indigenous Land of the same name, on the border with Bolivia. Firstly, we will address the sociology of these people and the way in which the relationships between clan and ethnicity cannot be easily elaborated based on a Euclidean topology. Then, based on the myths of the emergence of humanity and the relationships that indigenous people maintain with their owners and spirits, we will evaluate the notion of “humanity” and how it is subject to variation based on encounters. Finally, we will address the topic of witchcraft based on an accusation that occurred in the village of Ricardo Franco. We will think about how this concept is mobilized to talk about the effect caused by the chicha, which would be like that caused by the boa constrictor, a real hunt.